A comparison of serum fructosamine, 25-hydroxyvitamin D, calcium, and phosphorus levels in the first, second, and third trimester in obese and non-obese pregnant women with and without gestational diabetes mellitus - Nadimibarforoushi, Mohammadreza; Qujeq, Durdi; Roudi, Bostan (International journal of diabetes in developing countries, 2019)
Previous study demonstrated that obesity and associated gestational diabetes mellitus (GDM) are increasing. However, the combination of obesity and GDM contribute to the pregnancy complication have yet to be elucidated. The aim of this study was to compare serum fructosamine, 25-hydroxyvitamin D, calcium, and phosphorus levels in the first, second, and third trimester in obese and non-obese pregnant women with and without gestational diabetes mellitus. We performed a prospective, case-control study in 30 obese women diagnosed with GDM, 30 non-obese pregnant women with GDM, and 30 non-obese and without GDM, age-matched pregnant women who were enrolled in the first, second, and third trimester and followed-up until delivery. Blood samples were collected once from each participant in the first trimester of pregnancy, during the fetal viability scan, once in the second trimester of gestation during screening for gestational diabetes mellitus, and once in the third trimester of gestation. Serum fructosamine, 25-hydroxyvitamin D, calcium, and phosphorus levels were measured. In the third trimester, fructosamine level (1.8 ± 0.08) was slightly higher in obese women who were diagnosed with GDM than in the second and first trimester (1.70 ± 0.12, 1.70 ± 0.09), respectively. But, in the third trimester, phosphorus levels were slightly lower in GDM women who were GDM women than in the first trimester. In the first, second, and third trimester, in these subjects, the mean levels of vitamin D and calcium were slightly different. Our data tend to support the concept that fructosamine, 25-hydroxyvitamin D, calcium, and phosphorus level assays can provide a good index of health control especially in obese. This study has increased our knowledge of biochemical changes in GDM among obese pregnant women with GDM.